2017
DOI: 10.1108/yc-06-2017-00702
|View full text |Cite
|
Sign up to set email alerts
|

The young luxury consumer in Qatar

Abstract: Purpose This study aims to examine the factors influencing Qatari youth’s attitude toward luxury brands and intentions to purchase luxury brands. The appetite for luxury spending in the Gulf region and specifically in Qatar is accelerating even with the fall in oil prices and faltering economic growth. Design/methodology/approach Both qualitative research in the form of in-depth interviews and quantitative research in the form of survey were utilized in this study. Initially, eight in-depth interviews were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 34 publications
5
16
1
Order By: Relevance
“…The findings are consistent with the theoretical assumptions that underpinned the study and were in line to the findings obtained by Eng and Bogaert (2010) and Jiang and Shan (2018). This result confirms the fact that experiences play a huge role today for millennial consumers (Fromm, 2018; Farrag, 2017).…”
Section: Discussion and Findingssupporting
confidence: 91%
“…The findings are consistent with the theoretical assumptions that underpinned the study and were in line to the findings obtained by Eng and Bogaert (2010) and Jiang and Shan (2018). This result confirms the fact that experiences play a huge role today for millennial consumers (Fromm, 2018; Farrag, 2017).…”
Section: Discussion and Findingssupporting
confidence: 91%
“…The effect of quality on purchase intention of buying luxury brands was supported by the finding of the study. As this result is confirmed with what (Farrag, 2017) said which is that the opinion of the managers of luxury stores, who she had interviewed in Qatar, emphasized that the Qatari consumers used quality as an indicator of their luxury consumption. Nevertheless, even though, some studies stated that Asian countries are more materialistic than European ones (Li and Zhang, 2011), but this wasn't the case in Qatar as the findings of this study showed that materialism didn't have a significant impact on the consumer intention of buying luxury brands in Qatar.…”
Section: Conclusion and Implicationsupporting
confidence: 81%
“…Nevertheless, even though, some studies stated that Asian countries are more materialistic than European ones (Li and Zhang, 2011), but this wasn't the case in Qatar as the findings of this study showed that materialism didn't have a significant impact on the consumer intention of buying luxury brands in Qatar. Even though, the result supports (Farrag, 2017) İşletme Araştırmaları Dergisi Journal of Business Research-Turk 2201 research which conducted research about what affect young consumers in Qatar to purchase luxury brands. (Farrag, 2017) excluded materialism of her study factors based on exploratory research.…”
Section: Conclusion and Implicationsupporting
confidence: 59%
See 2 more Smart Citations